Study on PON Based LTE Small Cell Backbaul Tecbnology - Min Cao; Ming Jiang; Chengbin Shen; Tao Zeng (Dianxin kexue)
Technical requirements for LTE small cell backhaul networks were investigated. The feasibility and necessity of LTE small cell backhaul based on PON were presented in detail, which covered the factors such as TCO, technical capability, engineering and etc. Those key technologies related to PON based LTE small cell backhaul and their implementations were discussed. Finally, the progress of standardization, status of chipset and equipment development, typical cases of deployment and field trial, were introduced.